Hypogonadism in chronic liver disease: impaired release of luteinising hormone. Issue 6556 (8th November 1986) - Bannister, P; Handley, T; Chapman, C; Losowsky, M S
Abstract : Alcohol abuse leads to impotence, infertility, and feminisation. Patients with chronic alcoholism may have impaired hypothalamic-pituitary function. The release of luteinising hormone was investigated in men with alcoholic cirrhosis with and without hypogonadism and controls. Blood was sampled every 15 minutes for six or eight hours and luteinising hormone concentrations measured by radioimmunoassay. Data were analysed by iterative computerised analysis and spectral analysis to assess pulsatile release and the length of the cycle, respectively. Pulsatile release of luteinising hormone was shown in all the control subjects; in the men with alcoholic liver disease it was normal in those with subclinical primary testicular failure but absent or grossly attenuated in those with overt combined central and primary gonadal failure. The impaired release of luteinising hormone in the men with overt gonadal failure might be due to a hypothalamic defect.